Analisis Kinerja Algoritme Rowwise 1-D Partitioning dan 2-D Partitioning untuk Operasi Matriks pada Pemrosesan Paralel berbasis Rasberry Pi 3 - Dedy Eka Prasetya; Wijaya Kurniawan; Mochammad Hannats Hanafi Ichsan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Parallel processing is a process which use more than one of CPU or processor as data processing. On the parallel processing there are some methods which use for data processing and applied on the algorithm. That methods are OpenMPI which is standard programming that have work prociple distributed memory and OpenMP that have work principle or processing use shared memory. The both methods will be used on the parallel processing which applied on two multiplication matrix vector algorithms.That algorithms are Rowwise 1-D Partitioning and 2-D Partitioning. The algorithm of Rowwise 1-D Partitioning and 2-D Partitioning will be processed in parallel on OpenMPI and OpenMP. Parallel processing on two algorithms to matrix vector multiplication will be applied on Raspberry Pi 3 device. To access Rasberry Pi 3 use putty application for do remote access and WinSCP application for know the directory where the program is stored. Therefore, Rasberry Pi 3 in this research is as main processor on parallel processing matrix vector multiplication to Rowwise 1-D Partitioning and 2-D Partitioning algorithms. The performance from the both of these algorithms will be compared to get results in terms of efficiency and effectiveness.